Tráfico de órgãos humanos : análise à luz do ordenamento jurídico-penal e da (bio) ética - Buonicore, Giovana Palmieri (2013)
This dissertation analyzes the trafficking of human organs through the law prism - penal and (bio) ethical, in order to suggest the body dignity as a well-legal to be protected this offense. For this purpose, organ transplants are presented from the concept to the Brazilian panorama of this reality. After this brief presentation and conceptualization, organ trafficking is discussed in many ways such as why the nomenclature is used and the real cases about this thematic. Brazilian laws and other countries that belongs to Mercosul are also presented in order to demonstrate how these countries penalize it or not trafficking organs. Also pursues a juridical and penal organ trafficking analysis, explaining each penal type of law 9.434/97, as well as the theory of well- legal - penal, suggesting the body dignity as the well-legal to be protected. Besides that, human dignity and other fundamental rights are examined and related to the body dignity. Finally, aims to analyze (bio) ethically the offenses presented, relating ethics, bioethics through its principles, freedom and autonomy with body dignity.